The Production of An Interactive E-Module in the Course of Concepts and Aplications Building Information Modelling Civil Engineering Department - Assyura, Maulin; Yandra, Muvi (CIVED, 2024)
This research was motivated by the problems that exist during initial observations, namely the absence of learning media in the form of modules on the learning process of Concepts and Applications Building Information Modeling (BIM) course. Based on these problem, this study was aim to create a valid and practical learning media in the form of an Revit Structure interactive electronic module (e-module) for the Concepts and Applications of Building Information Modelling (BIM) course. This study uses the Research and Development (R&D) method which adapts the DDD-E model. The instrument used is a learning media assessment questionnaire for media experts, material experts, and students. Based on product evaluation of Revit Structure interactive electronic module-based learning media on the course of Concept and Application BIM by media experts from all aspects obtaining an assessment of 93,1% with very valid criteria, while assessment by material experts from all aspects obtained an assessment of 85.8% with very valid criteria. The assessment with the small trial stage with 8 students as respondents obtained an average score of 89.4% which was categorized as very practical and the large-scale testing stage with 18 students as respondents obtained an average value of 91,2% which was categorized as very practical. Based on the results of the assessment, the resulting media was declared feasible and practical to use for interactive electronic module-based learning media on the Concept and Aplication of Building Information Modelling course.